Microstructure Characterization of Pigeon Hole Rock Models at Different Scale: A Preliminary Study - Umar Fauzi (Institut Teknologi Bandung, 2007)
Microstructure of rocks determines physical properties of rocks at different scale, i.e.: from micro to giga scales. Study on microstructure characterization of rock models at different scale is conducted in this research. Rock models are generated using fractal pigeon hole models at zero level. Substructure ratio selected in this study is 22 with quotient of self-similarity equals to 0.25. Porosity of created models varies from 4 to 20%. Physical parameters, i.e.: porosity, specific surface area and two point correlation functions as well as hydraulic radius distribution, are evaluated for different pixel length. Physical parameters at small scales tend to have large deviation. The deviation decreases as the pixel length increases and tends to a similar value or trend at a specific length. This study shows that some characteristic lengths are available at several rock models.